1990
DOI: 10.1002/neu.480210711
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of the central nervous system of Drosophila

Abstract: The study of the metamorphosis of the central nervous system of Drosophila focused on the ventral CNS. Many larval neurons are conserved through metamorphosis but they show pronounced remodeling of both central and peripheral processes. In general, transmitter expression appears to be conserved through metamorphosis but there are some examples of possible changes. Large numbers of new, adult-specific neurons are added to this basic complement of persisting larval cells. These cells are produced during larval l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(212 citation statements)
references
References 27 publications
4
206
0
2
Order By: Relevance
“…Sensory neurons originate from the periphery during embryogenesis or from imaginal disks during metamorphosis and send projections into the CNS, which itself contains only motoneurons and interneurons (Palka et al, 1984;Hartenstein, 1988). Near the end of larval development, the CNS is composed of two distinct classes of neurons-functional ones, which arose during embryogenesis, and nonfunctional "adult-specific" neurons, which accumulated throughout larval development (Truman and Booker, 1986;Truman, 1990). Although some neurons in abdominal regions of the ventral CNS die during the first hours after pupariation, most neurons in the brain and thoracic regions appear to survive metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory neurons originate from the periphery during embryogenesis or from imaginal disks during metamorphosis and send projections into the CNS, which itself contains only motoneurons and interneurons (Palka et al, 1984;Hartenstein, 1988). Near the end of larval development, the CNS is composed of two distinct classes of neurons-functional ones, which arose during embryogenesis, and nonfunctional "adult-specific" neurons, which accumulated throughout larval development (Truman and Booker, 1986;Truman, 1990). Although some neurons in abdominal regions of the ventral CNS die during the first hours after pupariation, most neurons in the brain and thoracic regions appear to survive metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although some neurons in abdominal regions of the ventral CNS die during the first hours after pupariation, most neurons in the brain and thoracic regions appear to survive metamorphosis. Many larval motoneurons, for instance, survive, some changing their peripheral targets and others innervating (adult) targets for the first time (Truman, 1990). Serotonergic, catecholaminergic, and some peptidergic larval interneurons also persist into adult stages with only a few cells added in the optic lobe or central brain regions during metamorphosis (White et al, 1986;Budnick and White, 1988;Valles and White, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, studies from model organisms have identified intrinsic and extrinsic factors that can regulate pruning processes. For example, many axons and dendrites in Drosophila at larval stages are extensively pruned during metamorphosis (Truman 1990). Ecdysone is a major extrinsic factor that triggers metamorphosis: It is conceivable that an ecdysone receptor and a homolog of mammalian retinoic acid receptor are required cell-autonomously for the pruning (Lee et al 2000;Luo and O'Leary 2005).…”
Section: Guidance Molecules In Axon Pruning Intrinsic and Extrinsic Fmentioning
confidence: 99%
“…In any case, responsiveness to 20E is unlikely to be unique to MB neurons because many other neurons express EcR both in vivo and in vitro. The likely targets of 20E action during early pupal development include other larval neurons that are re-elaborating processes (Vallés and White, 1988;Truman, 1990) and newly born imaginal neurons (Ito and Hotta, 1992) that are generating processes de novo.…”
Section: Pupal Mb Neurons Respond To 20e In Vitromentioning
confidence: 99%